Specificity of DNA binding activity of the Bacillus subtilis catabolite control protein CcpA. - Kim, J H (1995)
CcpA was purified from Escherichia coli BL21 (lambda DE3)/pLysS carrying plasmid pTSC5, which was constructed by inserting the ccpA gene into the polycloning site of pGEM4. The purified protein migrated in sodium dodecyl sulfate-polyacrylamide gel electrophoresis with an apparent mass of 38 kDa but was eluted from a calibrated Bio-Gel P-100 column with an apparent mass of 75 kDa. Western blot (immunoblot) analysis revealed the presence of CcpA in E. coli BL21 (lambda DE3)/pLysS/pTSC5, which carries ccpA, and in wild-type Bacillus subtilis 168 but not in E. coli BL21 (lambda DE3)/pLysS/pGEM4 or in B. subtilis WLN-29, in which ccpA is inactivated by transposon Tn917 insertion. Purified CcpA bound to DNA containing amyO and retarded its mobility in electrophoretic mobility shift analysis. Complete retardation of the DNA required 75 ng of CcpA per assay. In DNase protection analysis, CcpA bound to DNA containing amyO and protected a region spanning amyO when either DNA strand was labeled. Mutant forms of amyO not effective in catabolite repression were not retarded by CcpA.